Age of onset of bipolar disorder: Combined effect of childhood adversity and familial loading of psychiatric disorders. (October 2016) - Post, Robert M.; Altshuler, Lori L.; Kupka, Ralph; McElroy, Susan L.; Frye, Mark A.; Rowe, Michael; Grunze, Heinz; Suppes, Trisha; Keck, Paul E.; Leverich, Gabriele S.; Nolen, Willem A.
Abstract: Background: Family history and adversity in childhood are two replicated risk factors for early onset bipolar disorder. However, their combined impact has not been adequately studied. Methods: Based on questionnaire data from 968 outpatients with bipolar disorder who gave informed consent, the relationship and interaction of: 1) parental and grandparental total burden of psychiatric illness; and 2) the degree of adversity the patient experienced in childhood on their age of onset of bipolar disorder was examined with multiple regression and illustrated with a heat map. Results: The familial loading and child adversity vulnerability factors were significantly related to age of onset of bipolar and their combined effect was even larger. A heat map showed that at the extremes (none of each factor vs high amounts of both) the average age of onset differed by almost 20 years (mean = 25.8 vs 5.9 years of age). Limitations: The data were not based on interviews of family members and came from unverified answers on a patient questionnaire. Conclusions: Family loading for psychiatric illness and adversity in childhood combine to have a very large influence on age of onset of bipolar disorder. These variables should be considered in assessment of risk for illness onset in different populations, the need for early intervention, and in the design of studies of primary and secondary prevention.